Impact of Headteachers’ Leadership Styles on Teachers’ Job Performance in Sagnarigu Municipality in Northern Region of Ghana - Sarah, Mahamudu; Iddrisu Bariham; Joseph Yaw Dwamena Quansah (Social Education Research, 2023)
Teachers’ productivity and job performance in educational settings are significantly dictated by several factors, including the leadership styles employed by headteachers in the governance of schools. However, there is an ongoing debate among scholars in educational management as to which school governance style is the most effective and can facilitate high productivity among teachers. This research was therefore carried out to explore the effects of headteachers’ leadership styles on the job performance of junior high school teachers in Sagnarigu Municipality in Ghana’s Northern Region. The research adopted cross-sectional design informed by three research questions. Out of 82 schools, Yamane (1967) formula for sample size determination was used to randomly sample (N = 68 school heads) to complete a Questionnaire for Headteachers’ Leadership Style (QHLS). Using Cronbach alpha formula, the reliability of the items on the questionnaire was validated. The Standardized Lesson Observation Scale (SLOS) was used to observe the instructional quality of 40 teachers. The study found excellent performance of teachers in quality lesson delivery with female teachers out-performing the males. Also, the sampled schools had more male teachers than females. The democratic leadership style was the most frequently used by headteachers with autocratic leadership approach being the least utilized. There was no statistically significant relationship between headteachers’ leadership styles and job performance of teachers. The demographic characteristics of headteachers have no statistically significant influence on their leadership styles. The study recommends recruitment of more females as headteachers, capacity building for heads of schools, and periodic organization of Continuous Professional Development (CPD) programs.